Effects of a postbiotic, with and without a saponin-based product, on turkey performance - Evan Chaney; Elizabeth A. Miller; Jeffrey Firman; Andrea Binnebose; Vivek Kuttappan; Timothy J. Johnson (Poultry Science, 2023)
ABSTRACT: Modern poultry production relies on an ability to prevent and mitigate challenges to bird health, while maintaining a productive bird. A number of different classes of biologics-based feed additives exist, and many have been tested individually for their impacts on poultry health and performance. Fewer studies have examined the combinations of different classes of products. In this study, we examined the use of a well-established postbiotic feed additive (Original XPC, Diamond V) on turkey performance, with and without the addition of a proprietary saponin-based feed additive. This was accomplished in an 18-wk pen trial utilizing 22 pen replicates per treatment across 3 treatments (control, postbiotic, and postbiotic plus saponin). Significant differences in body weight were identified at wk 12 and 15 of age, with the postbiotic plus saponin treatment group resulting in heavier birds at both timepoints. Significant differences in feed conversion ratio were observed from 0 to 18 wk of age, with the postbiotic alone having improved FCR compared with the control group. No significant differences were observed for livability or feed intake. This study demonstrates that a combination of a postbiotic plus saponin may exert additive effects on the growth of the turkey.